A battery positive electrode composition and preparation method thereof

The use of yttrium metaphosphate and polyacrylonitrile coatings, along with zinc doping, stabilizes the nickel cobalt manganese oxide structure, addressing electrochemical and safety issues in high-nickel lithium-ion batteries, enhancing their performance and stability.

CN118867250BActive Publication Date: 2024-12-27GUANGZHOU KAIJIE POWER SUPPLY INDAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327824.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

High-nickel positive electrode materials in lithium-ion batteries suffer from poor electrochemical performance, safety issues, and interface instability due to cation mixing, lithium residue reactions, and microcrack formation, which degrade battery capacity and safety.

Method used

A battery positive electrode composition comprising a modified nickel cobalt manganese oxide core coated with yttrium metaphosphate and polyacrylonitrile, combined with controlled zinc doping, to stabilize the structure and reduce residual alkali compounds, thereby enhancing electrochemical and safety performance.

Benefits of technology

The proposed composition effectively reduces residual alkali compounds, inhibits anisotropic lattice changes, and prevents cracking, resulting in improved electrochemical performance and safety, with enhanced energy density and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867250B_ABST
    Figure CN118867250B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a battery positive electrode composition and a preparation method thereof. The battery positive electrode composition provided by the present invention includes a positive electrode active material, a conductive agent and an adhesive; the positive electrode active material includes a core and a coating layer, the core is a modified nickel cobalt manganese oxide positive electrode material, and the coating layer is yttrium metaphosphate and polyacrylonitrile. The present invention uses Y(PO3)3 to coat the modified nickel cobalt manganese oxide positive electrode material, effectively reducing the residual alkali compounds on the surface of the positive electrode material, and uses polyacrylonitrile to further coat the Y(PO3)3 coated positive electrode material, effectively improving the electrochemical performance and safety performance of the battery; zinc is used to dope and modify the nickel cobalt manganese oxide positive electrode material to inhibit the formation of microcracks and improve the electrochemical performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a battery positive electrode composition and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have become the main power source in portable electronic products, energy storage systems, and new energy vehicles due to their advantages such as no memory effect, high energy density, and environmental friendliness. Among the various components of lithium-ion batteries, the positive electrode material plays a decisive role in core indicators such as cost, safety, and energy density. Therefore, optimizing the positive electrode material is the key to improving the performance of lithium-ion batteries.

[0003] In the field of positive electrode materials, high nickel material LiNi x M 1-x O2 (x ≥ 0.6, M = Mn, Co, Al, etc.) has attracted the attention of researchers and become a research hotspot due to its advantages such as high specific capacity and low cost. It is considered to be an ideal positive electrode material for lithium-ion power batteries at this stage. However, as the nickel content of high-nickel materials continues to increase, the mixing of cations in the positive electrode materials becomes more and more serious, resulting in a decrease in battery capacity. In addition, the lithium residue on the surface of high-nickel materials and the serious side reactions between high-nickel materials and electrolytes cause the electrochemical performance and safety performance of lithium-ion batteries to deteriorate, and the formation of microcracks further aggravates the interface side reactions. Therefore, a well-designed positive electrode-electrolyte interface is conducive to improving the stability of high-nickel materials and obtaining lithium-ion batteries with high energy density and long cycle life.

[0004] The Chinese patent application document with publication number CN109704413A discloses a high-nickel positive electrode material, wherein the high-nickel positive electrode material has a chemical formula of LiNi x Co y Mn z Al 1-x-y-z O2 indicates that the method for improving the storage performance of the high-nickel positive electrode material is to mix a manganese-containing inorganic salt, an aluminum-containing inorganic salt, LiOH·H2O and a high-nickel precursor, add ethanol and grind them evenly to obtain a solid powder mixture, pre-calcine the obtained solid powder mixture, and then heat it to calcine to obtain the high-nickel positive electrode material. This method effectively inhibits the side reaction of the high-nickel positive electrode material with moisture and carbon dioxide in the air, improves the surface stability of the material, and thus improves the storage stability of the material, but it does not solve the problem of poor anti-leakage safety performance of lithium batteries. Summary of the invention

[0005] In order to solve the technical problems existing in the related art such as poor electrochemical performance and safety performance of lithium batteries, poor interface stability, etc., the purpose of the present invention is to provide a battery positive electrode composition and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] A battery positive electrode composition, comprising the following components and their weight proportions:

[0008] 85-90 parts of positive electrode active material, 3-5 parts of conductive agent, and 5-10 parts of binder; the positive electrode active material includes a core and a coating layer, the core is a modified nickel cobalt manganese oxide positive electrode material, and the coating layer is yttrium metaphosphate and polyacrylonitrile.

[0009] In the preparation process of nickel cobalt manganese oxide positive electrode materials, an excess of lithium source is usually added to make up for the loss of lithium in the electrochemical reaction process, and the addition of excess lithium is beneficial to reduce the degree of cation mixing in the battery. Therefore, a large amount of residual lithium is attached to the surface of the nickel cobalt manganese oxide positive electrode material, and the residual lithium on the surface will react with CO2 and H2O in the air to generate residual alkali compounds such as LiOH and Li2CO3, which will affect Li + Migration. In addition, LiOH will react with the positive electrode electrolyte LiPF6 to generate HF, and HF will react with Li2CO3 to generate CO2 gas, affecting the safety and cycle performance of the battery. In the present invention, Y(PO3)3 and polyacrylonitrile are used to coat the modified nickel cobalt manganese oxide positive electrode material, wherein Y(PO3)3 can react with residual alkali compounds to form mixed phosphates during the sintering process, forming LiPO3, Y(PO3)3, Li3PO4, YPO4 and other compounds on the surface, effectively reducing the residual alkali compounds on the surface of the positive electrode material and improving the electrochemical properties and safety performance of the positive electrode material; polyacrylonitrile contains a cyano group with a strong electronegativity, which can react with Ni in the positive electrode material. 2+ 、Co 3+ The cations undergo coordination and have good ductility, which can effectively wrap the positive electrode material, inhibit the anisotropic lattice change of the positive electrode material, alleviate the stress concentration inside the positive electrode material particles, avoid material cracking, and improve the safety performance of the battery.

[0010] Furthermore, the preparation method of the modified nickel cobalt manganese oxide positive electrode material is: 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor and lithium hydroxide are mixed, ground evenly, and then zinc oxide is added and ground evenly; the obtained mixture is placed in a tubular furnace, oxygen is introduced, the temperature is raised to 500-550°C and calcined for 4-4.5h, and the temperature is continued to be raised to 700-740°C and calcined for 12-14h, cooled, and ground to obtain a modified nickel cobalt manganese oxide positive electrode material.

[0011] The precursor (Ni 0.90 Co 0.05 Mn 0.05(OH)2) was purchased from Ningbo Rongbai Technology Co., Ltd. In the present invention, zinc is used to dope and modify the nickel cobalt manganese oxide positive electrode material to improve the structural stability of the nickel cobalt manganese oxide positive electrode material, inhibit the formation of microcracks, and thus improve the electrochemical performance of the lithium ion battery.

[0012] Furthermore, in the preparation method of the modified nickel cobalt lithium manganese oxide positive electrode material, Ni 0.90 Co 0.05 Mn 0.05 The total molar ratio of nickel, cobalt and manganese in the (OH)2 precursor to the molar ratio of lithium hydroxide is 2-5:7-9, and the molar ratio to zinc oxide is 11-13:1.

[0013] In the present invention, by controlling Ni 0.90 Co 0.05 Mn 0.05 The doping amount of zinc oxide is controlled by the ratio of the total molar number of nickel, cobalt and manganese in the (OH)2 precursor to the molar number of zinc oxide. It is found that although zinc oxide can improve the structural stability of the nickel cobalt manganese oxide lithium positive electrode material and inhibit the generation of microcracks, when the amount of zinc oxide exceeds the range specified by the present invention, zinc doping will cause lattice changes and cation mixing of the nickel cobalt manganese oxide lithium positive electrode material, thereby affecting the electrochemical properties of the lithium ion battery.

[0014] Furthermore, the preparation method of the positive electrode active material is as follows: (1) adding yttrium metaphosphate to anhydrous ethanol, adding modified nickel cobalt manganese oxide positive electrode material after ultrasonic vibration, stirring for 1-1.5 hours and then heating to 90-95°C, continuing to stir until the anhydrous ethanol is completely volatilized, transplanting into a tubular furnace after drying, passing oxygen, sintering at 550-600°C for 5.5-6 hours, cooling, grinding, and obtaining a powder material; (2) dissolving acrylonitrile in N,N-dimethylformamide, adding the powder material obtained in step (1), heating to 85-90°C under stirring, keeping warm for reaction for 2-3 hours, placing in a tubular furnace after drying, passing argon, sintering at 200-250°C for 1.5-2 hours, and obtaining a positive electrode active material.

[0015] Furthermore, the amount of yttrium metaphosphate used in step (1) of the method for preparing the positive electrode active material is 2%-5% of the mass of the modified lithium nickel cobalt manganese oxide positive electrode material.

[0016] Furthermore, in the preparation method of the positive electrode active material, the ultrasonic oscillation in step (1) has an ultrasonic frequency of 300-400 kHz and a duration of 30-40 min.

[0017] Furthermore, the amount of acrylonitrile used in step (2) of the method for preparing the positive electrode active material is 0.5%-1% of the mass of the powder material.

[0018] Furthermore, the conductive agent is one of conductive carbon black, graphene, graphite, and acetylene black.

[0019] Furthermore, the adhesive is one of sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber.

[0020] The present invention also provides a method for preparing the battery positive electrode composition, which specifically comprises: mixing the positive electrode active material and the conductive agent, stirring them evenly, adding a binder, and stirring them evenly to obtain the battery positive electrode composition.

[0021] Compared with the prior art, the battery positive electrode composition and the preparation method thereof provided by the present invention have the following technical advantages:

[0022] (1) In the present invention, Y(PO3)3 is used to coat the modified nickel cobalt manganese oxide positive electrode material, which effectively reduces the residual alkali compounds on the surface of the positive electrode material and improves the electrochemical performance and safety performance of the positive electrode material;

[0023] (2) In the present invention, the positive electrode material coated with Y(PO3)3 is further coated with polyacrylonitrile, which can not only reduce the interface reaction of the positive electrode material and inhibit the anisotropic lattice change of the positive electrode material, but also alleviate the stress concentration inside the positive electrode material particles, avoid material cracking, and improve the safety performance of the battery;

[0024] (3) In the present invention, zinc is used to dope and modify the nickel cobalt manganese oxide positive electrode material, thereby improving the structural stability of the nickel cobalt manganese oxide positive electrode material, inhibiting the formation of microcracks, and further improving the electrochemical performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the modified nickel cobalt lithium manganese oxide positive electrode material prepared in Example 3;

[0026] Figure 2 This is a scanning electron microscope image of the modified nickel cobalt lithium manganese oxide positive electrode material prepared in Example 4. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is clearly and completely described below in conjunction with specific embodiments. The specific embodiments described are only partial embodiments of the present invention, rather than limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0028] In this specific embodiment, the precursor (Ni 0.90 Co 0.05 Mn 0.05(OH)2) was purchased from Ningbo Rongbai Technology Co., Ltd. The preparation method of the battery positive electrode composition is: the positive electrode active material and the conductive agent are mixed, stirred evenly, and then a binder is added, stirred evenly, to obtain the battery positive electrode composition.

[0029] Example 1

[0030] A battery positive electrode composition, comprising the following components and their weight proportions:

[0031] 85 parts of positive electrode active material, 5 parts of conductive carbon black, and 10 parts of sodium carboxymethyl cellulose; the positive electrode active material includes a core and a coating layer, the core is a modified nickel cobalt manganese oxide positive electrode material, and the coating layer is yttrium metaphosphate and polyacrylonitrile.

[0032] The preparation method of the modified nickel cobalt lithium manganese oxide positive electrode material is: 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor and lithium hydroxide are mixed, and the ratio of the total molar number of nickel, cobalt and manganese to the molar number of lithium hydroxide is 2:7. After grinding evenly, zinc oxide is added, and the ratio of the total molar number of nickel, cobalt and manganese to the molar number of zinc oxide is 11:1. Grind evenly; the obtained mixture is placed in a tubular furnace, oxygen is introduced, the temperature is raised to 500°C and calcined for 4.5 hours, and the temperature is continued to be raised to 700°C and calcined for 14 hours. Cool and grind to obtain a modified nickel cobalt manganese oxide lithium positive electrode material.

[0033] The preparation method of the positive electrode active material is as follows: (1) adding yttrium metaphosphate to anhydrous ethanol, ultrasonically oscillating at 300kHz for 40 minutes, adding modified nickel cobalt lithium manganese oxide positive electrode material, wherein the amount of yttrium metaphosphate is 2% of the mass of the modified nickel cobalt lithium manganese oxide positive electrode material, stirring for 1 hour, heating to 90°C, continuing to stir until the anhydrous ethanol is completely volatilized, and transplanting into a tubular furnace after drying, introducing oxygen, sintering at 550°C for 6 hours, cooling, grinding, and obtaining a powder material; (2) dissolving acrylonitrile in N,N-dimethylformamide, adding the powder material obtained in step (1), wherein the amount of acrylonitrile is 0.5% of the mass of the powder material, heating to 85°C under stirring, keeping the temperature for reaction for 3 hours, and placing in a tubular furnace after drying, introducing argon, and sintering at 200°C for 2 hours to obtain a positive electrode active material.

[0034] Example 2

[0035] A battery positive electrode composition, comprising the following components and their weight proportions:

[0036] 90 parts of positive electrode active material, 3 parts of graphite, and 5 parts of polyacrylic acid; the positive electrode active material includes a core and a coating layer, the core is a modified nickel cobalt manganese oxide positive electrode material, and the coating layer is yttrium metaphosphate and polyacrylonitrile.

[0037] The preparation method of the modified nickel cobalt lithium manganese oxide positive electrode material is: 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor and lithium hydroxide are mixed, the ratio of the total molar number of nickel, cobalt and manganese to the molar number of lithium hydroxide is 5:9, and zinc oxide is added after grinding evenly, the ratio of the total molar number of nickel, cobalt and manganese to the molar number of zinc oxide is 13:1, and grinding evenly; the obtained mixture is placed in a tubular furnace, oxygen is introduced, the temperature is raised to 550°C and calcined for 4 hours, and the temperature is continued to be raised to 740°C and calcined for 12 hours, cooled, and ground to obtain a modified nickel cobalt manganese oxide lithium positive electrode material.

[0038] The preparation method of the positive electrode active material is as follows: (1) adding yttrium metaphosphate to anhydrous ethanol, ultrasonically oscillating at 400kHz for 30 minutes, adding modified nickel cobalt lithium manganese oxide positive electrode material, the amount of yttrium metaphosphate being 5% of the mass of the modified nickel cobalt lithium manganese oxide positive electrode material, stirring for 1.5 hours, heating to 95°C, continuing to stir until the anhydrous ethanol is completely volatilized, transplanting into a tubular furnace after drying, passing oxygen, sintering at 600°C for 5.5 hours, cooling, grinding, and obtaining a powder material; (2) dissolving acrylonitrile in N,N-dimethylformamide, adding the powder material obtained in step (1), the amount of acrylonitrile being 1% of the mass of the powder material, heating to 90°C under stirring, keeping warm for reaction for 2 hours, placing in a tubular furnace after drying, passing argon, and sintering at 250°C for 1.5 hours to obtain a positive electrode active material.

[0039] Example 3

[0040] A battery positive electrode composition, comprising the following components and their weight proportions:

[0041] 88 parts of positive electrode active material, 4 parts of acetylene black, and 8 parts of styrene-butadiene rubber; the positive electrode active material includes a core and a coating layer, the core is a modified nickel cobalt manganese oxide positive electrode material, and the coating layer is yttrium metaphosphate and polyacrylonitrile.

[0042] The preparation method of the modified nickel cobalt lithium manganese oxide positive electrode material is: 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor and lithium hydroxide are mixed, and the ratio of the total molar number of nickel, cobalt and manganese to the molar number of lithium hydroxide is 3:8. After grinding evenly, zinc oxide is added, and the ratio of the total molar number of nickel, cobalt and manganese to the molar number of zinc oxide is 12:1. Grind evenly; the obtained mixture is placed in a tubular furnace, oxygen is introduced, the temperature is raised to 530°C and calcined for 4.2h, and the temperature is continued to be raised to 730°C and calcined for 13h. Cool and grind to obtain a modified nickel cobalt manganese oxide lithium positive electrode material.

[0043] The preparation method of the positive electrode active material is as follows: (1) adding yttrium metaphosphate to anhydrous ethanol, ultrasonically vibrating at 350kHz for 35 minutes, adding modified nickel cobalt lithium manganese oxide positive electrode material, the amount of yttrium metaphosphate being 4% of the mass of the modified nickel cobalt lithium manganese oxide positive electrode material, stirring for 1.2 hours, heating to 93°C, continuing to stir until the anhydrous ethanol is completely volatilized, transplanting into a tubular furnace after drying, passing oxygen, sintering at 580°C for 5.8 hours, cooling, grinding, and obtaining a powder material; (2) dissolving acrylonitrile in N,N-dimethylformamide, adding the powder material obtained in step (1), the amount of acrylonitrile being 0.8% of the mass of the powder material, heating to 88°C under stirring, keeping the temperature for reaction for 2.5 hours, placing in a tubular furnace after drying, passing argon, and sintering at 230°C for 1.7 hours to obtain a positive electrode active material.

[0044] Comparative Example 1

[0045] The battery positive electrode composition in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of lithium metaphosphate is used instead of yttrium metaphosphate in this comparative example.

[0046] Comparative Example 2

[0047] The battery positive electrode composition in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that yttrium oxide is used instead of yttrium metaphosphate in this comparative example.

[0048] Comparative Example 3

[0049] The battery positive electrode composition in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that in step (2) of the preparation method of the positive electrode active material in this comparative example, an equal amount of acrylic acid is used instead of acrylonitrile.

[0050] Comparative Example 4

[0051] The battery positive electrode composition described in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that zinc oxide is not added in the preparation method of the modified nickel cobalt manganese oxide positive electrode material described in this comparative example.

[0052] Comparative Example 5

[0053] The battery positive electrode composition described in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that in the preparation method of the modified nickel cobalt manganese oxide positive electrode material described in this comparative example, the ratio of the total molar number of nickel, cobalt and manganese to the molar number of zinc oxide is 2:3.

[0054] Comparative Example 6

[0055] The battery positive electrode composition described in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that in the preparation method of the modified nickel cobalt manganese oxide positive electrode material described in this comparative example, the ratio of the total molar number of nickel, cobalt and manganese to the molar number of zinc oxide is 1:1.

[0056] Test example

[0057] Residual alkali content test: Take 10 g of the positive electrode active material prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3, dissolve it in 10 mL of deionized water (solid content 50%), stir it at room temperature for 15 min and then dry it, and test the surface residual alkali content with reference to GB / T 41704-2022.

[0058] Preparation of button cells: The battery positive electrode compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 6 are coated on aluminum foil and dried in a vacuum oven at 100°C; then the electrode sheets are cut out using a slicer with a diameter of 14 mm and dried in a vacuum oven at 80°C for 6-12 hours; then the cells are transferred to an argon-filled glove box, and assembled into button cells using a metal lithium sheet as the counter electrode, a polypropylene porous membrane as the diaphragm, and a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate as the electrolyte.

[0059] Safety performance test: Take the button cells made of the battery positive electrode compositions of Examples 1 to 3 and Comparative Examples 1 to 3, and charge and discharge the button cells in the range of 3.0V-4.45V (0.1C). After the third charge to 4.45V, disassemble the battery, take out the positive electrode material, wash off the electrolyte on the surface with a solvent (the composition is 1.15 mol / L LiPF6, the solvent is EC:EMC=7:3), and then dry it. Then, refer to the method of GB / T19466.5-2022 (Part 5 of Differential Scanning Calorimetry DSC for Plastics) for differential scanning calorimetry DSC test, the heating rate is 2°C / min, and the decomposition temperature and heat release of the material are recorded.

[0060] Discharge specific capacity test: Take the button batteries made of the battery positive electrode compositions of Examples 1 to 3 and Comparative Examples 1 to 6, charge them to 4.2V at 0.2C constant current at 30°C, and then switch to constant voltage charging with a cut-off current of 0.05C; discharge the battery to 2.75V at 0.2C constant current, and obtain the capacity of the battery discharged to 3.0V at room temperature with 0.2C current, which is the battery discharge capacity; then charge the battery to 4.2V at 0.2C constant current, remove the battery and weigh the battery weight m at this time, and obtain the discharge specific capacity based on calculation; discharge specific capacity = battery discharge capacity / battery weight.

[0061] Battery capacity retention rate test: Take the button cell made from the battery positive electrode composition of Example 1 to Example 3 and Comparative Example 1 to Comparative Example 6, charge the battery to 4.2V at 1C constant current, then switch to constant voltage charging, with a cut-off current of 0.05C; then, discharge the battery to 3.0V at 1C constant current. Repeat the above steps 100 times, and obtain the capacity of the battery discharged to 3.0V at 1C current after 200 cycles at room temperature, and calculate the battery capacity retention rate after the cycle; capacity retention rate = discharge capacity after cycle / first discharge capacity × 100%.

[0062] The test results are shown in Table 1.

[0063] Table 1 Performance test results

[0064]

[0065] As shown in Table 1, the residual alkali content of the battery positive electrode compositions obtained in Examples 1 to 3 is less than 1400ppm, the button batteries prepared using the battery positive electrode compositions obtained in Examples 1 to 3 have a decomposition temperature of 253-276°C, a decomposition heat release of 712-737J / g, a discharge specific capacity of 259.7-276.5mAh / g, and a 200-cycle discharge capacity retention rate of 99.7%-99.9%, which fully demonstrates that the battery positive electrode composition provided by the present invention has good electrochemical performance and safety performance. The battery positive electrode composition obtained in Example 3 has the best performance in all aspects and is the best embodiment of the present invention.

[0066] Compared with Example 3, in Comparative Example 1, an equal amount of lithium metaphosphate was used instead of yttrium metaphosphate, but the residual alkali content of the button cell obtained was slightly increased, and the discharge specific capacity and discharge capacity retention rate were reduced. This shows that although lithium metaphosphate can also react with residual alkali compounds, its effect is obviously not as good as yttrium metaphosphate; in Comparative Example 2, yttrium oxide was used instead of yttrium metaphosphate, but the residual alkali content of the button cell obtained was increased, and the discharge specific capacity and discharge capacity retention rate were reduced. This shows that although yttrium oxide can achieve the coating of the positive electrode material, it cannot reduce the residual alkali content, and the improvement of the electrochemical performance of the battery is obviously not as good as yttrium metaphosphate; in the preparation method of the positive electrode active material in Comparative Example 3, an equal amount of acrylic acid was used instead of acrylonitrile in step (2), but the button cell obtained was The decomposition temperature of the button battery is significantly reduced, and the decomposition heat release is significantly increased, which indicates that polyacrylonitrile achieves effective packaging of the positive electrode material and effectively improves the safety performance of the battery; in the preparation method of the modified nickel cobalt manganese oxide positive electrode material in Comparative Example 4, zinc oxide is not added, but the discharge specific capacity and discharge capacity retention rate of the button battery obtained are reduced, which indicates that the modification of the nickel cobalt manganese oxide positive electrode material by zinc oxide can effectively improve the electrochemical performance of the battery; Comparative Examples 5 and 6 change the ratio of the total molar number of nickel, cobalt, and manganese to the molar number of zinc oxide in the preparation method of the modified nickel cobalt manganese oxide positive electrode material, but the discharge specific capacity and discharge capacity retention rate of the button battery obtained are reduced, which indicates that the amount of zinc oxide used has a key influence on the electrochemical performance of the battery.

[0067] Scanning electron microscope test: The modified nickel cobalt lithium manganese oxide positive electrode material prepared in Example 3 and the modified nickel cobalt lithium manganese oxide positive electrode material prepared in Comparative Example 4 were tested by scanning electron microscope. Figure 1 This is a scanning electron microscope image of the modified nickel cobalt lithium manganese oxide positive electrode material obtained in Example 3. Figure 2 This is a scanning electron microscope image of the modified nickel cobalt lithium manganese oxide positive electrode material prepared in Example 4. Figure 1 and Figure 2 It can be seen that zinc oxide doped modified nickel cobalt manganese oxide positive electrode material can effectively inhibit the formation of microcracks.

[0068] The above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any person skilled in the art shall not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, any modification, equivalent substitution and improvement made by those skilled in the art under the technical concept of the present invention shall still be covered by the claims of the present invention.

Claims

1. A battery positive electrode composition, characterized in that: It includes the following components and their weight parts: 85-90 parts of positive electrode active material, 3-5 parts of conductive agent, and 5-10 parts of binder; the positive electrode active material includes a core and a coating layer, the core is a modified nickel cobalt manganese oxide positive electrode material, and the coating layer is yttrium metaphosphate and polyacrylonitrile; The preparation method of the modified nickel cobalt lithium manganese oxide positive electrode material is: 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor and lithium hydroxide are mixed, ground evenly, and then zinc oxide is added and ground evenly; the obtained mixture is placed in a tube furnace, oxygen is introduced, the temperature is raised to 500-550°C and calcined for 4-4.5h, and the temperature is further raised to 700-740°C and calcined for 12-14h, cooled, and ground to obtain a modified nickel cobalt manganese oxide positive electrode material; the Ni 0.90 Co 0.05 Mn 0.05 The total molar ratio of nickel, cobalt and manganese in the (OH)2 precursor to the molar ratio of lithium hydroxide is 2-5:7-9, and the molar ratio to zinc oxide is 11-13:

1.

2. The battery positive electrode composition according to claim 1, characterized in that: The preparation method of the positive electrode active material is as follows: (1) adding yttrium metaphosphate to anhydrous ethanol, adding modified nickel cobalt manganese oxide positive electrode material after ultrasonic vibration, stirring for 1-1.5 hours and heating to 90-95°C, continuing to stir until the anhydrous ethanol is completely volatilized, transplanting into a tubular furnace after drying, introducing oxygen, sintering at 550-600°C for 5.5-6 hours, cooling, grinding, and obtaining a powder material; (2) dissolving acrylonitrile in N,N-dimethylformamide, adding the powder material obtained in step (1), heating to 85-90°C under stirring, keeping warm for reaction for 2-3 hours, placing in a tubular furnace after drying, introducing argon, and sintering at 200-250°C for 1.5-2 hours to obtain a positive electrode active material.

3. The positive electrode composition of a battery according to claim 2, characterized in that: The amount of yttrium metaphosphate used in step (1) is 2%-5% of the mass of the modified nickel cobalt manganese oxide positive electrode material.

4. The battery positive electrode composition according to claim 2, characterized in that: The ultrasonic oscillation in step (1) has an ultrasonic frequency of 300-400 kHz and a duration of 30-40 min.

5. The battery positive electrode composition according to claim 2, characterized in that: The amount of acrylonitrile used in step (2) is 0.5%-1% of the mass of the powder material.

6. The battery positive electrode composition according to claim 1, characterized in that: The conductive agent is one of conductive carbon black, graphene, graphite and acetylene black.

7. The battery positive electrode composition according to claim 1, characterized in that: The adhesive is one of sodium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber.

8. The method for preparing a positive electrode composition for a battery according to any one of claims 1 to 7, characterized in that: Specifically, the positive electrode active material and the conductive agent are mixed, stirred evenly, and then a binder is added and stirred evenly to obtain a battery positive electrode composition.